PENDEKATAN SOSIOLOGI DALAM STUDI ISLAM - Dahniar (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
The presence of religion today is required to be actively involved in solving various problems faced by mankind. Religion should not only be used as a symbol of piety, but conceptually able to show effective ways to solve problems. Such guidance on religion can be answered when the understanding of religion which has so far used a normative theological approach is complemented by an understanding of religion that uses other approaches that operationally can provide answers to problems that arise. These various approaches include normative theological, anthropological, sociological, psychological, historical, cultural and philosophical approaches. The importance of a sociological approach in understanding religion can be understood because there are so many religious teachings related to social problems. Through a sociological approach, religion will be understood easily, because religion itself is derived for social purposes.